Ben Ammi Ben Israel: black theology, theodicy and Judaism in the thought of the African Hebrew Israelite Messiah - Miller, Michael T. (Bloomsbury studies in black religion and cultures, 2023)
"Investigates the many books and speeches of Ben Ammi, the African Hebrew Israelite spiritual leader, providing a comprehensive introduction to his thought in the context of both African American and Jewish contemporaries and precursors"--